COVID-19 Surveillance Enhanced by an Integrated Electronic Infectious Diseases Information System in Albania. (March 2022) - Mersini, K.; Vasili, A.; Sulo, J.; Bashllari, A.; Moci, A.; Zefi, V.; Agolli, L.; Fico, A.; Bino, S.
Abstract : Purpose: The objective of this paper is to showcase how COVID -19 control has been enhanced by interrelating syndromic surveillance, case based surveillance and laboratory surveillance and outbreak investigation into an integrated electronic Infectious Diseases Information System (IDIS). Methods & Materials: Development of IDIS began in December 2016 with the goal to modernize the Albanian surveillance system by developing a user-friendly, comprehensive database for case investigation, contact tracing, and laboratory data focusing on the improvement of the timeliness indicators of disease detection and response. The platform is based on open-source software solutions featuring (1) integration of data from different surveillance systems such as indicator, syndromic and event base; (2) better investigation and management of outbreaks and reduced data-entry time and errors (3) generation of line listing and contact-tracing and workflows to appropriately follow-up of cases and contacts; (4) integration with the national vaccination registry for retrieving vaccination history and prospectively apply ring vaccinations during outbreak control; (5) integration with laboratory information system public and private to retrieve diagnostic information; and (6) repository with qualitative and quantitative cache of epidemiological information and data; Results: The IDIS system has assisted public health surveillance to document COVID-19 cases and to take disease control actions such as case isolation, contact tracing and contact isolation, and more recently vaccination. To date 400.000 potential cases of COVID -19 have been notified in the system has been notified 273.000 have been individually investigated. About 487.000 laboratory results have been linked with case based information and respective contacts. The system has proved useful for data analysis as a series of epidemiological indicators have been calculated to inform evidence based decision making in controlling COVID-19 epidemic in Albania. Conclusion: IDIS implementation has improved the consistency, communication, and effective use of public health data. In particular integration of different surveillance systems and workflows which are developed within IDIS provide an array of instruments to epidemiologists to detect cases faster, make better decisions based on multiple data sources and more effectively plan response measures.